Alcohol use in South Sudan in relation to social factors, mental distress and traumatic events. (December 2016) - Lien, Lars; Hauff, Edvard; Martinez, Priscilla; Eide, Arne; Swarts, Leslie; Ayazi, Touraj
Abstract Background Alcohol use is a major public health problem with vast implications for poor, war-torn countries. The objective of this study was to describe prevalence of alcohol use and risky drinking across socio-demographic factors in South Sudan, and to determine the association between risky drinking, traumatic events and mental distress. Methods This is a randomized, population based, cross-sectional study from the north-western part of South Sudan with nearly 500 participants. We used the Alcohol Use Disorders Identification Test (AUDIT) as main outcome variable, the General Health Questionnaire (GHQ-28) for mental distress and five questions to assess traumatic events. Results The mean AUDIT score was 2.7 (SD 0.3) with 14, 2 % in the high risk problem drinking category. Being male, lack of a regular income and psychological distress were significantly associated with higher AUDIT score. Traumatic events, however, was not associated with higher score on AUDIT. Conclusion Despite decades of civil war and great poverty the alcohol use in this population was at the same level as other countries in Southern Africa. Traumatic events were not related to risk of problem drinking.